Do Vietnamese upland farmers benefit from high world market prices for maize?. (27th September 2015) - Luckmann, Jonas; Ihle, Rico; Kleinwechter, Ulrich; Grethe, Harald
Abstract: For rural households in the north of Vietnam, maize cropping is the main source of income. In the face of the world market price increases of the recent past, we analyze the regional marketing chain of this commodity qualitatively and econometrically investigating to what extent smallholder farmers in developing countries are affected by international price movements. Vietnamese maize markets are found to be well integrated. Recent price hikes have fully transmitted along the regional supply chain so that farmers profited. Nevertheless, adverse factors such as increasing input prices have neutralized these benefits resulting in a decline in real income of smallholders.